Mobile Counselling Online an Alternative Counselling Guidance System For Millennial Era Student - Fahyuni, Eni Fariyatul; Taurusta, Cindy; Hariastuti, Retno Tri; Bandono, Adi; Muhid, Abdul (Journal of Education Technology, 2021)
This study analyses the counselling service system during the COVID-19 pandemic on introducing potential and preparation of learning strategies for junior and senior high school in the Sidoarjo district. This research design is a mixed-method with quantitative and qualitative approaches using exploratory factor analysis and further research and development (R&D) to produce products in online counselling guidance services. The results of the exploratory factor analysis qualitatively reveal various problems experienced and needed by students during the COVID-19 pandemic. In contrast, quantitatively, shows that eight forms of Counselling guidanceservices, the strengthening of skill skor 0.999 is the highest. Its effect on increasing students' self-efficacy and achievement motivation. The findings of this study indicate that students need online counselling services in recognizing their learning potential and problems. Hereafter, online counselling guidance must three factors: understanding the potential for effective learning, designing and developing learning strategies, and building students' internal and external motivation. The innovation of online counselling guidance must consider the factors of convenience, convenience, and user confidentiality services that are adaptive, flexible and unlimited in the millennial era.